Education as a Catalyst: School-Based Strategies to Prevent Child Marriage in Lombok, Indonesia - Suliyana Suliyana; Insof Waeji (Muslim Education Review, 2025)
Child marriage as a pressing issue in Indonesia significantly impacts education, economic and societal dynamics. This study focuses on the Lombok region, a place with a high prevalence of child marriages; investigating its factors, impacts, and strategies. Utilizing a qualitative case study design, data were collected from deep interviews with teachers across five schools in Lombok. Findings reveal that cultural traditions, alongside economic challenges and lack of family support, contribute to this practice. Child marriage has an impact on education, fosters psychological problems, and perpetuates poverty. Furthermore, all dimensions from both factors to impacts have a high correlation with education. Education interventions play a significant role in addressing this practice. Strategies such as school-community collaboration, parental involvement, and additional activities are highlighted, though their effectiveness is hindered by deep-rooted cultural norms. Despite challenges, schools are crucial in promoting awareness, fostering education, and supporting systems for at-risk youth. This study headlines the need for comprehensive policies integrating education and socio-economic support to prevent child marriage in Lombok comprehensively. It contributes to understanding localized contexts.